An Analysis of English Teachers’ Creativity in Media-Based Learning at the Tenth-Grade Students - Epria Primsa Meliala; Pebri Wati Romatua Purba; Lavia Panjaitan; Likawati Doloksaribu; Natalia Widya-Pasca Tarigan (Journal of Languages and Language Teaching, 2021)
This study aims to describe English teachers' creativity in using learning media in the tenth grade students at SMK Pencawan Medan. This study is descriptive qualitative. The data were obtained by interview. The data analysis followed some steps, namely collecting data, reducing, display data, data verification and create reports. The results showed that teachers employed the various teaching-learning media in ELT classes. English teachers used various media to make it easier for students to learn and understand the teaching materials. The media include audio, visual, and audiovisual. The most media used in the ELT classes were audio and visual. A small portion of media was made through internet sources. But the teacher has not been optimal in carrying it out,  it can be seen from when the teacher uses PowerPoint media, teachers applied it imperfect, and not every day the teacher uses learning media to achieve learning goals. Based on the conclusion above, the researchers give suggestion to the teachers should always looking for creative new things and create active, innovative, and fun learning, and also motivate students to seriously participate in learning even though they study through online.